Steganography in GIF animated grayscale images - Yerlan, Massalin (2013)
Computer steganography is the one of the most rapidly developing areas, because for a long time it was underestimated and neglected. The computer steganography gives an opportunity to embed information within a digital object, at the same time, striving to minimize the impact on the carrier object. One of the most popular carrier media are still images due to their immense popularity in the Internet compared with other formats of digital objects such as video or audio formats. And one of the most suitable formats from among still images is BMP format, due to the absence of compression loss and larger capacity, that allows to hide larger amounts of data, than for example, JPEG images. Herewith, the author proposes an survey in the area of Bitmap images. So there is a certain logic in our work, when we start from BMP survey and proceed to an animated GIF format, since the frames inside GIF format are of BMP format as well. And we propose an algorithm based on LSB method, that selectively changes the LSB according to the properties in the images.